Modifying effect of obesity on the association between sitting and incident diabetes in post‐menopausal women. (4th December 2013) - Manini, Todd M.; LaMonte, Michael J.; Seguin, Rebecca A.; Manson, JoAnn E.; Hingle, Melanie; Garcia, Lorena; Stefanick, Marcia L.; Rodriguez, Beatriz; Sims, Stacy; Song, Yiqing; Limacher, Marian
<x xml:space="preserve">Abstract</x> Objective To evaluate the association between self‐reported daily sitting time and the incidence of type 2 diabetes in a cohort of postmenopausal women. Methods Women (N=88, 829) without diagnosed diabetes reported the number of hours spent sitting over a typical day. Incident cases of diabetes were identified annually by self‐reported initiation of using oral medications or insulin for diabetes > 14.4 years follow‐up. Results Each hour of sitting time was positively associated with increased risk of diabetes [risk ratio (RR): 1.05; 95% confidence interval (CI): 1.02–1.08]. However, sitting time was only positively associated with incident diabetes in obese women. Obese women reporting sitting 8–11 (RR: 1.08; 95% CI 1.0–1.1), 12–15 (OR: 1.13; 95% CI 1.0–1.2), and ≥16 hours (OR: 1.25; 95% CI 1.0–1.5) hours per day had an increased risk of diabetes compared to women sitting ≤7 hours per day. These associations were adjusted for demographics, health conditions, behaviors (smoking, diet, and alcohol intake), and family history of diabetes. Time performing moderate to vigorous intensity physical activity did not modify these associations. Conclusions Time spent sitting was independently associated with increased risk of diabetes diagnosis among obese women—a population already at high risk of the disease.